EFFORTS TO PREVENT BULLYING BEHAVIOR THROUGH UNDERSTANDING BRAHMAVIHĀRA STUDENTS OF KERTARAJASA BUDDHIS COLLEGE - Febrianti, Ira (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
This study aims to determine efforts to prevent bullying behavior through understanding Brahmavihāra second semester students of STAB Kertarajasa, Batu, Academic Year 2021/2022. The research method used is explanatory. The sampling in this study was purposive sampling by determining 5 people as key informants. Data collection was carried out by in-depth interviews with informants with experience gained in understanding and applying brahmavihāra. Data analysis used the Miles and Huberman method, namely data collection, data condensation, data display, and conclusion drawing or verification. The results of the study found that almost all STAB Kertarajasa students had experienced bullying behavior with various manifestations. The negative impacts felt varied from feelings of lack of confidence, inferiority, and excessive shame from the social environment. In addition, it was found that some of them had carried out bullying behavior even though the action was considered normal and was a mere joke. After gaining understanding and applying brahmavihāra gradually, the mindset of the second semester students of STAB Kertarajasa began to change. That it is very important to always understand and respect each other in order to create a harmonious atmosphere. Brahmavihāra as a foundation in coexistence among others and can prevent acts of bullying that often occur in the surrounding environment.